Megafon för människans tidsålder: En kritisk diskursanalys av miljöfrågans framställning på Riksidrottsmuseum - Berg, John (Idrott, historia och samhälle, 2026)
The article analyses selected parts of the permanent exhibitions at The National Sports Museum in Stockholm, Sweden, focusing on how environmental issues are presented. The analysis is deepened through theories about museology and the Anthropocene, the age of man, and the ways in which the museum addresses human responsibility and role in critical environmental issues. Through a critical discourse analysis in which the exhibitions are analysed in relation to the governing documents of the Swedish sports movement, conclusions are drawn that The National Sports Museum presents environmental issues from a clearly anthropocentric perspective. The most obvious findings indicate that environmental issues, in addition to being given relatively low priority by the museum, are presented as if they should not stand in the way of continued development in sport. Furthermore, environmental issues should primarily be solved through technological advances, which signals a strong belief in human ability. The anthropocentric approach is also evident in the museum’s exhortation to visitors to take individual responsibility for addressing and solving environmental issues.